Burnout Akademik di Era Digital dan Persepsi Mahasiswa terhadap Peluang Pemanfaatan Artificial Intelligence untuk Deteksi Dini - Wafiq, Ainun; Syawal, Ahmad; ., Ikrar; Ahmad, Zainal Arifin (Jurnal Sains dan Teknologi (JSIT), 2025)
The phenomenon of academic burnout in the digital era is increasingly concerning as students face academic pressures exacerbated by intensive digital technology demands, yet no studies in Indonesia have integrated student experiences with potential AI-based solutions for early detection. This study aims to explore student experiences with academic burnout, identify digital indicators perceived as burnout markers, and analyze student perceptions of the feasibility and acceptance of AI utilization for early burnout detection. Using a qualitative approach with case study methods, data were collected through in-depth interviews and focus group discussions (FGDs) with 16 purposively selected Master's students in Islamic Education Management at UIN Sunan Kalijaga. Data analysis employed Braun & Clarke's thematic analysis using Job Demands-Resources and Technostress Model frameworks. Results indicate that student academic burnout is associated with unregulated digital activity patterns operating through four mediation mechanisms: sleep disruption, cognitive overload, social comparison, and boundary erosion. Students identify five main digital indicators: excessive screen time, notification overload, activity polarization, digital sleep disturbance, and social isolation. Regarding AI, students exhibit ambivalence: optimistic about AI's potential as an objective "digital mirror," yet demanding fulfillment of five ethical principles (algorithm transparency, informed consent, non-surveillance, privacy by design, empowerment-centered) as prerequisites for acceptance.